Pelatihan Teknologi Alat Kesehatan Digital bagi Kader Posyandu Pasca Bencana Cianjur: Upaya Pemenuhan Hak atas Kesehatan Berdasarkan Perspektif Hukum dan Kebijakan Publik - Sulaeman, Fietri Setiawati; Handayani, Trini; Nazilah, Siti; Mulyana, Aji; Bintang, Muhammad (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2025)
The earthquake that struck Cianjur Regency in November 2022 severely damaged health facilities and disrupted routine medical services, including maternal and child healthcare. Training on the use of digital health technology for Posyandu (integrated health post) cadres serves as a strategic intervention to ensure the continuity of essential healthcare services in post-disaster settings. This activity, part of the 2023 Kosabangsa Program, aimed to enhance the capacity of cadres in early detection of health issues such as Chronic Energy Deficiency (CED) and heart rhythm disorders by utilizing tools like the digital Upper Arm Circumference (LILA) Calculator, Heart Rate Device, and body temperature monitors based on microcontrollers and IoT technology. This training aligns with the fulfillment of the right to health as mandated by Article 28H of the 1945 Constitution and Law Number 36 of 2009 concerning Health, and supports the implementation of public policies on disaster management in accordance with Law Number 24 of 2007. The results show increased understanding and skills among cadres in operating digital health tools, along with active community participation in restoring healthcare services. Thus, the training contributes not only to medical technical aspects but also to the fulfillment of the community’s constitutional right to equitable and sustainable health services. Keywords: Tools; Health; Technology; Training.